Miniaturized and high-performance RF packages with ultra-thin glass substrates. (July 2018) - Kim, Min Suk; Pulugurtha, Markondeya Raj; Kim, Youngwoo; Park, Gapyeol; Cho, Kyungjun; Smet, Vanessa; Sundaram, Venky; Kim, Joungho; Tummala, Rao
Abstract: Advanced RF packages are demonstrate with active (low-noise amplifier, RF switch) and passive integration in ultra-thin 3D glass packages with miniaturization and enhanced performance. The novelty of this RF packages is three-fold: 1) Ultra-thin 100 μm glass, 2) Double-side thinfilm RF circuits interconnected with Through-Package Vias (TPVs), and 3) Direct assembly of the glass-core package to the board with Land Grid Array (LGA) connections. An innovative double-via process, starting from prefabricated vias in bare glass, polymer filling and via drilling, is utilized for a robust and high-yield substrate fabrication process. Scalable and low-cost panel laminate processes are utilized to form the RF circuits on the build-up layers. The performance benefits are demonstrated through interconnect loss, impedance match, electrical gain and noise figure measurements. Compared to existing RF substrates, the glass substrates show 2.5X miniaturization in substrate thickness with extensibility to thinner substrates.